Effects of an expressive writing intervention on cancer‐related distress in Danish breast cancer survivors — results from a nationwide randomized clinical trial. Issue 7 (19th September 2012) - Jensen‐Johansen, M. B.; Christensen, S.; Valdimarsdottir, H.; Zakowski, S.; Jensen, A. B.; Bovbjerg, D. H.; Zachariae, R.
Abstract Objective To examine the effects of an expressive writing intervention (EWI) on cancer‐related distress, depressive symptoms, and mood in women treated for early stage breast cancer. Methods A nationwide sample of 507 Danish women who had recently completed treatment for primary breast cancer were randomly assigned to three 20‐min home‐based writing exercises, one week apart, focusing on either emotional disclosure (EWI group) or a non‐emotional topic (control group). Cancer‐related distress [Impact of Event Scale (IES)], depressive symptoms (Beck Depression Inventory—Short Form), and negative (37‐item Profile of Moods State) and positive mood (Passive Positive Mood Scale) were assessed at baseline and at 3 and 9 months post‐intervention. Choice of writing topic (cancer versus other), alexithymia (20‐item Toronto Alexithymia Scale), and social constraints (Social Constraints Scale) were included as possible moderators. Results Significant (p < 0.01) group differences in mood change from before to immediately after each session suggested successful manipulation. Reductions over time in psychological symptoms were seen in both groups (p < 0.05), but no time × group interactions were found. Choice of writing topic moderated effects on IES, with women writing about other themes showing greater reductions in cancer‐related avoidance than women writing about their cancer. Fewer depressive symptoms and higher levels of positive mood were seen 3 months post‐intervention in women writing about their cancer when compared with the control group. Difficulties describing feelings and externally oriented thinking (20‐item Toronto Alexithymia Scale) moderated effects on positive mood and IES‐total, while no moderating effects were found of social constraints. Conclusions In concordance with the majority of previous results with cancer patients, no main effects of EWI were found for cancer‐related distress, depressive symptoms, and mood. Moderator analyses suggested that choice of writing topic and ability to process emotional experiences should be studied further. Copyright © 2012 John Wiley & Sons, Ltd.